Cross-linked graphene oxide sheets via modified extracted cellulose with high metal adsorption. (15th September 2017) - Yakout, Amr A.; El-Sokkary, Ramadan H.; Shreadah, Mohamed A.; Abdel Hamid, Omnia G.
Highlights: Preparation of cross-linked graphene oxide sheets, where immobilized grafted cellulose was used as cross-linker. Cellulose was extracted from mangrove trees ( Avicennia marina ) roots pulp. The cross-linked sheets were successfully employed for the removal of Cu(II) and Pb(II) ions from wastewater samples. Abstract: We have studied the extraction of Cu(II) and Pb(II) ions from different types of aqueous solution by novel cross-linked graphene oxide sheets by modified extracted cellulose. The novel sorbent cellulose was extracted from the mangrove trees ( Avicennia marina ) and it was then grafted with acrylamide and immobilized by ethylenediamine for cross-linking process. The cross-linked graphene oxide sheets were identified by means of FT-IR, SEM and XRD. The adsorption studies of synthesized sorbent was optimized. Langmuir and Freundlich models were used for establish sorption equilibria. The cross-linked graphene oxide sheets showed maximum adsorption capacity 46.39 and 186.48 mg g −1 for Cu(II) and Pb(II), respectively. The potential applications of this sorbent was applied to remove Cu(II) and Pb(II) metal ions from hard water samples by using a multi-stage micro-column technique.